2012
DOI: 10.1515/1556-3758.2593
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Spray Drying On Physical Properties, Total Phenolic Content And Antioxidant Activity Of Carob Molasses

Abstract: In the present study carob molasses (pekmez) was spray dried to obtain a powder with desired improved handling properties. Maltodextrin with dextrose equivalent (DE) values of 8.6, 15.3 and 18.6 was used as a drying agent. Different molasses to maltodextrin ratios (25:75, 50:50), and dryer air inlet temperatures (160°C, 210°C) were additional parameters. The spray dried powders were analyzed for glass transition temperature, moisture content, water activity, wetting behavior, particle size, color, total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
2
16
0
4
Order By: Relevance
“…With an increase in inlet temperature, glass transition temperatures decreased. Similar results were reported by Akkaya et al [22] for spray drying of carob molasses. These T g values were in the same range as those reported for acai powders obtained by spray drying using maltodextrin [25].…”
Section: Water Solubility Index (Wsi) and Water Absorption Index (Wai)supporting
confidence: 91%
See 1 more Smart Citation
“…With an increase in inlet temperature, glass transition temperatures decreased. Similar results were reported by Akkaya et al [22] for spray drying of carob molasses. These T g values were in the same range as those reported for acai powders obtained by spray drying using maltodextrin [25].…”
Section: Water Solubility Index (Wsi) and Water Absorption Index (Wai)supporting
confidence: 91%
“…In the first stage, most of the drying occurs as a result of free moisture vaporization from the surface of the droplet. In the second stage, drying rate is lowered as a result of crust formation at the drop surface and the concentration of unbound water to the inner part of the droplet [22]. Especially for sugar-rich products, evaporation is controlled by moisture diffusion in the crust [23].…”
Section: Powder Analysismentioning
confidence: 99%
“…The average values of TPC 369 retention for all types of citrus extracts were more than 80%. High 370 recoveries of phenolic compounds during spray drying have also 371been reported in several studies[9,28], which suggested that spray 372 drying is suitable for heat-sensitive materials such as phenolic 373 compounds. A previous study has also reported that the spray-374 drying temperatures did not affect the retention of TPC signifi-…”
mentioning
confidence: 89%
“…A sample cup was half-filled with dragon fruit peel, then the water activity was measured using a pre-calibrated water activity meter (AquaLab, Model CX2, Decagon Devices, Pullman, WA, USA) [16].…”
Section: Water Activitymentioning
confidence: 99%